Predictors of health literacy among older adults with hypertension in Bali, Indonesia: A cross-sectional study - Krisnayanti, Putu Mega; Promnoi, Chantra; Chinnawong, Tippamas (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: The prevalence of hypertension in Indonesia continues to increase, particularly in Bali. However, existing research focusing on health literacy in Indonesia, especially among older adults with hypertension, is still limited and outdated. Objective: This cross-sectional predictive design study aimed to examine the level of health literacy among older adults with hypertension and its associated factors. Methods: Two hundred ninety-six eligible older adults with hypertension were purposively selected from two regencies in Bali. Data were collected from March to April 2025 using the Demographic Characteristic Questionnaire, the Short-Form Health Literacy Survey (HLS-SF12), the Perceived Severity of Illness Questionnaire (PSIQ), and the Multidimensional Scale of Perceived Social Support (MSPSS). The data were analyzed using descriptive statistics and multiple regression. Results: The findings showed an adequate level of health literacy among older adults with hypertension. The regression model explained 47.80% of the variance in health literacy (R² = 0.478). Significant associated factors of health literacy included perceived severity of illness (β = 0.353, p < 0.001), social support (β = 0.347, p < 0.001), and social activity engagement (β = 0.166, p < 0.001). However, use of media (β = 0.039, p = 0.375) and access to healthcare services (β = 0.001, p = 0.977) were not statistically significant predictors of health literacy among older adults with hypertension. Conclusion: Perceptions of illness severity, along with social support and social activity engagement, play a fundamental role in shaping the health literacy of older adults with hypertension in Bali. These findings can guide nurses in developing a tailored education program to help older adults better understand illness severity and promote social integration.